Yours the Power : Faith-Based Organizing in the USA. - Day, Katie. (Religious Studies, Theology and Philosophy E-Books Online, Collection 2013, ISBN: 9789004248748., 2013)
Despite shifts in the religious landscape in North America--reflected in the significant increase in those with no religious affiliation and emptier pews across the religious spectrum--there has also been a rise in participation in faith-based grassroots organizations. People of faith are increasingly joining broad-based organizing efforts to seek social change in their communities, regions and country. This unique volume brings together the most current thinking on faith-based organizing from the perspective of theologians, social researchers and practitioners. The current state of faith based organizing is critically presented, as it has evolved from its roots in the mid-twentieth century into a context which raises new questions for its philosophical assumptions, methodology, and very future. Originally published as issue 4 of Volume 6 (2012) of Brill's International Journal of Public Theology .